11-Keto-β-Boswellic Acids Prevent Development of Autoimmune Reactions, Insulitis and Reduce Hyperglycemia During Induction of Multiple Low-Dose Streptozotocin (MLD-STZ) Diabetes in Mice - Shehata, A. M.; Quintanilla-Fend, L.; Bettio, S.; Jauch, J.; Scior, T.; Scherbaum, W. A.; Ammon, H. P. T. (Hormone and Metabolic Research, 2015)
The aim of the work was to study whether or not 11-keto-β-boswellic acids prevent induction of autoimmune reactions, insulitis, and hyperglycemia in the model of multiple low-dose streptozotocin (MLD-STZ) diabetes. Using male mice (n=6) diabetes was induced by daily i.p. injections of 40 mg/kg STZ for 5 days. In a second series together with STZ, daily i. p. injections of 11-keto-β-boswellic acid (KBA) and O-acetyl-11-keto-β-boswellic acid (AKBA) (7.5 and 15.0 mg/kg) were applied for 10 days. Thereafter, pro-and anti-inflammatory cytokines in the blood, histochemistry of pancreatic islets, and blood glucose levels were assayed. Five days after the last injection of STZ, a significant burst of pro-and anti-inflammatory cytokines in the blood, infiltration of lymphocytes (CD3) into pancreatic islets, and appearance of peri-insular apoptotic cells were observed. Plasma glucose increased significantly (124.4±6.65 vs. 240.2±27.36 mg/dl, p<0.05). Simultaneous treatment with KBA and AKBA significantly reduced pro-and anti-inflammatory cytokines (IFN-γ p<0.01, p<0.01; IL-1A p<0.001, p<0.001; IL-1B p<0.001, p<0.001; IL-2 p<0.001, p<0.001; IL-6 p<0.01, p<0.001; TNF-α p<0.05, p<0.001; IL-4 p<0.01, p<0.001; IL-10 p<0.001, p<0.001) in the blood. No infiltration of lymphocytes into pancreatic islets and appearance of peri-insular cells were detected. Moreover, KBA and AKBA reduced STZ-mediated increase of blood glucose on day 10 to 163.25±16.6 (p<0.05) and 187.6±19.5 mg/dl (p<0.05), respectively. In the model of MLD-STZ induced diabetes KBA and AKBA prevent cytokine burst, development of insulitis and reduce increase of blood glucose through “silencing” a forced-up immune reaction.
Keywords: boswellic acids; multiple low dose streptozotocin diabetes; prevention; insulitis; histochemistry; cytokines